Penolong yang Sepadan menurut Kejadian 2:18 terkait Perdebatan Kepemimpinan Wanita dalam Gereja - Stella, Yunita (Jurnal Teologi dan Pelayanan Kerusso, 2024)
The text of Genesis 2:18 is one of the passages debated by Complementarians and Egalitarians regarding the role of women as "helpers." Complementarians believe that the role of a helper indicates the functional subordination of women to men. According to them, Adam and Eve are spiritually equal, but Eve is not equal to Adam in function because she is his helper. For this reason, Complementarians refuse to place women in positions of leadership in the church. On the other hand, Egalitarians believe that women should have the same opportunities as men, including in church leadership. This study aims to analyze Genesis 2:18 in relation to the debate on women's leadership in the church. The method used is exegesis, to uncover the meaning according to the original author's intent when the text was written. The results of this study indicate that the helper provided by God is not a subordinate, but a partner. Women were created as partners to help their husbands so that God's mandate could be fulfilled through the unity of the two. This context applies to the household, not the church. Therefore, this role should not be used to prohibit women from teaching and leading in the church.